Determinants impacting foreign direct investment flows for developed and developing economies: an analysis based upon panel data set - ZIA UR REHMAN, MUHAMMAD (2018)
The research has been conducted to empirically analyze the foreign direct investments and the factors that cause foreign direct investments flowing in an economy. This study can be referred to as secondary and causal in nature, where the estimation models have been constructed on a panel dataset of 30 countries for a total of 18 years from 1996-2014. The main data source for collection of variables data has been The World Development Indicators. Multiple regression techniques have been applied using two different models with foreign direct investments as the dependent variable. The results indicate that FDI inflows are significantly impacted by labor wages level in an inverse relationship. Whereas, FDI has been found out to be positively associated with GDP growth rate, previous years FDI, domestic investments and trade openness.